2022-RA-598-ESGO Prognostic factors for adverse obstetric outcomes in pregnant cancer patients an update on 2174 cases registered in the INCIP registry. (20th October 2022) - Maggen, Charlotte; Heimovaara, Joosje; van Calsteren, Kristel; Cardonick, Elyce; Laenen, Annouschka; Shmakov, Roman G; Wolters, Vera; Gziri, Mina Mhallem; Lok, Christianne; Polushkina, Evgeniya; Blommaert, Jeroen; Halaska, Michael; et al.
Abstract : Introduction/Background: Following the increasing evidence on fetal safety, over time more pregnant women are receiving cancer treatment, including chemotherapy, in order to safeguard maternal prognosis. To evaluate current clinical practice obstetric and neonatal outcomes of women registered by the International Network on Cancer, Infertility and Pregnancy (INCIP) were assessed. Methodology: Women with a primary or recurrent invasive cancer during pregnancy or women who were pregnant while receiving invasive cancer treatment between 1996 and 2021 were selected from the INCIP database. Descriptive statistics on oncological diagnosis, stage, antenatal treatment, obstetric and neonatal outcomes, and reported complications was performed. Proportions of events were estimated per 5-year time period with 95% confidence intervals using logistic regression models. A logistic regression model was used to explore the relationship between cancer stage and type, antenatal treatment and obstetric outcome [preterm premature rupture of membranes (PPROM), (planned or spontaneous) preterm delivery, small for gestational age (SGA), other obstetric or medical complications, admission in the neonatal intensive care unit (NICU)], pregnancy loss (miscarriages and stillbirths) and maternal death. Multiple imputation was used to deal with missing data. Results: In the pregnant cancer population (n=2174), preterm delivery(47%), delivery by cesarean section (45%), planned delivery(65%), SGA(27%), maternal death (2%) and NICU admission (33%) are common. Over time, more women received antenatal chemotherapy(p<0.001), associated with an increase in SGA(p=0.07), spontaneous preterm delivery(p=0.009) and medical complications (p=0.002), and a decrease in elective preterm delivery(p<0.001), NICU admission (p=0.044) and neonatal complications(p<0.001). Most important prognostic factors for adverse outcomes were hematological cancers [maternal death OR 8.0, 95%CI(2.7–23.5), p<0.001], metastatic disease [maternal death OR 7.0, 95%CI(3.7–13.4), p<0.001, pregnancy loss OR 2.2, 95%CI(1.5–3.2), p<0.001] and antenatal chemotherapy [PPROM OR 2.6, 95%CI(1.9–3.5), p<0.001, SGA OR 1.6, 95%CI(1.3–2.1), p<0.001, other obstetric complications OR 1.6, 95%CI(1.2–2.2), p=0.003]. Conclusion: Antenatal chemotherapy will put a pregnancy at risk of complications and pregnant cancer patients should be managed in high risk obstetric units.